Gen Z Investment Decision: Role of Financial Literacy, Financial Behaviour, Financial Experience and Risk Tolerance - Tubastuvi, Naelati; Azaria, Muhammad Javier Fausta; Purwidianti, Wida; Aryoko, Yudhistira Pradhipta (Universitas Airlangga, 2024)
This research aims to investigate the determinants influencing investment decisions among Generation Z in Banyumas Regency, Indonesia. This research focuses on the population of Generation Z individuals aged 18-27 years, with a sample size of 120 respondents selected through purposive sampling using the 10-times rule method. Data collection was conducted using a structured questionnaire based on a Likert scale to assess various factors, including financial literacy, financial behaviour, financial experience, and risk tolerance. The analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM) using Smart PLS software, which facilitated the evaluation of both the outer and inner models to test validity, reliability, and hypothesis testing. The results show that financial literacy, financial behaviour and risk tolerance positively and significantly influence investment decisions among Generation Z respondents. These findings suggest that increasing financial literacy, improving financial behaviour and having good risk tolerance can lead to more informed investment decisions among this demographic. Meanwhile, financial experience does not affect investment decisions, indicating that Generation Z investors do not consider their financial experience in their investment decisions. The implications of this research highlight the importance of targeted financial education programs aimed at Generation Z to improve their investment decision-making capabilities. By fostering a better understanding of financial concepts and encouraging responsible financial behaviours, stakeholders can contribute to the development of a more financially literate and proactive generation of investors